Validation of “TOPRS” Score to Predict Outcome in Paediatric Patients in a Tertiary Care Hospital of Pakistan - Awan, Aamir Aslam; Nadeem, Muhammad Tariq; Babar, Bushra; Iftikhar, Ammara; Wahab, Abdul; Quddus, Abdul (Pakistan Armed Forces Medical Journal, 2023)
Objective: To validate a clinical scoring system for defining the severity of ailment that will assist in developing strategies for management prioritisation.Study Design: Cross-sectional analytical study.Place and Duration of Study: Paediatric Department, Combined Military Hospital Lahore, Pakistan, form Jan 2020 to Jul 2021.Methodology: The paediatric patients who reported to the Medical Reception Centre and were admitted to an Inpatient Facility were enrolled. Demographic profile, temperature, oxygen saturation, pulse, respiratory rate, seizures, and sensorium labelled as “TOPRS” score was recorded with “0 – Normal” and “1 – Abnormal” and scores calculated for each patient with the incorporation of systemic inflammatory response and advanced paediatric life support criteria. Results: A total of 300 paediatric patients with an age range of 1-18 years (mean: 3.86±5.43) were included. Of 300 patients, 237(79%) were discharged after improvement, and the mortality rate was 63(21%). A significant association with the mortality rate was deciphered with temperature, oxygen saturation, and respiratory rate variables. In contrast, pulse rate, sensorium, and seizures were concluded to have an insignificant association. Score “0” mortality was associated with the 4.4% mortality, whereas score “5” enumerated an 80% death rate.Conclusion: The TOPRS clinical scoring system has significant value in the diagnosis of mortality and morbidity of paediatric patients and, hence, can assist in early recognition and triage of patients, consequently aiding in the provision of prioritisation protocols and management in a befitting manner.